2016
DOI: 10.1002/bsl.2271
|View full text |Cite
|
Sign up to set email alerts
|

Juror Decision‐making in Death Penalty Sentencing when Presented with Defendant's History of Child Abuse or Neglect

Abstract: Previous studies have found aggravating, mitigating, and null effects of defendant histories of abuse and neglect on punishment preferences in capital sentencing. Perceiving these defendants as more dangerous, jurors may be more likely to favor the death penalty when such evidence is presented. This is counter to the intuition that abuse or neglect reduces culpability, and therefore mitigates the severity of punishment. We investigated the effect of defendant childhood physical abuse, sexual abuse, or neglect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…This suggests that for GBH and sexual offences, childhood maltreatment does not generate leniency from the public. This finding is interesting, and contradictory with previous research within the area that has shown public attitudes to either increase leniency or negativity when they are made aware of an offender's abusive childhood (e.g., Bell-Holleran et al, 2016;Butler & Jacquin, 2014). However, the present study did not specify the type of childhood abuse that the individual depicted in the vignette had experienced, only that was 'child abuse'.…”
Section: History Of Childhood Abusecontrasting
confidence: 99%
See 1 more Smart Citation
“…This suggests that for GBH and sexual offences, childhood maltreatment does not generate leniency from the public. This finding is interesting, and contradictory with previous research within the area that has shown public attitudes to either increase leniency or negativity when they are made aware of an offender's abusive childhood (e.g., Bell-Holleran et al, 2016;Butler & Jacquin, 2014). However, the present study did not specify the type of childhood abuse that the individual depicted in the vignette had experienced, only that was 'child abuse'.…”
Section: History Of Childhood Abusecontrasting
confidence: 99%
“…Interestingly, public attitudes towards people who offend are mixed when participants become aware of an offenders' abusive childhood. Sometimes this information can lead to public leniency (Bell-Holleran et al, 2016;Haegerich & Bottoms, 2000;Najdowski et al, 2009;Stalans & Henry, 1994) whereas in other instances, this knowledge can increase negative attitudes (Butler & Jacquin, 2014;Fabian, 2003;. Attribution Theory can help to explain these findings (Crisp & Turner, 2014;Shaver, 1985;Weiner, 2006).…”
mentioning
confidence: 99%
“…Several studies have shown that a history of child maltreatment has mitigating effects on sentencing decisions (e.g., Barnett, Brodsky, & Davis, ; Bell Holleran, Vaughan, & Vandiver, ; Lynch & Haney, ; Tetterton & Brodsky, ). For example, Bell Holleran et al () varied evidence concerning the nature of a defendant's childhood abuse in a mock capital trial and found large reductions in the likelihood of a death sentence in cases involving a defendant who had been sexually abused as a child, and moderate reductions for defendants who had been physically abused or neglected.…”
Section: Introductionmentioning
confidence: 99%
“…A study examining whether there was a difference between a history of neglect, physical abuse, or sexual abuse in militating a death sentence (Bell Holleran et al., 2016) found history of sexual abuse the most mitigating. Moderate mitigation was found for physical abuse, and minimal mitigation was found for neglect (Bell Holleran et al., 2016).…”
Section: Literature Reviewmentioning
confidence: 99%